(untitled) (KASBIT Business Journal, 2024)
Use of Accounting Information System (AIS) has become a significant research area since the computer software became prominent just over 3 decades ago. Therefore, the purpose of this study is to examine the factors determining the use of AIS and its influence on business performance in the manufacturing SMEs of Pakistan producing leather, surgical and sports goods. Drawing upon the Technology–Organization–Environment (TOE) theoretical framework, Diffusion of Innovations theory (DOI), and Resource-based theory (RBV), an interactive, comprehensive and multi-dimensional research framework was introduced. This research framework assessed the drivers of use of AIS by looking at technological, organizational, and environmental (TOE) factors as suggested in the TOE model. All these independent variables were used to predict the use of AIS and its impact on firm performance of Pakistani manufacturing SMEs producing leather, surgical and sports goods. Key words: AIS, Firm Performance, Manufacturing SMEs, TOE Model, DOI Theory, RBV, IT Literacy, Mediation, Moderation.